Development and validation of a mortality predicting scoring system for severe aplastic anaemia patients receiving haploidentical allogeneic transplantation. (6th November 2021) - Xu, Lan‐Ping; Yu, Yu; Cheng, Yi‐Fei; Zhang, Yuan‐Yuan; Mo, Xiao‐Dong; Han, Ting‐Ting; Wang, Feng‐Rong; Yan, Chen‐Hua; Sun, Yu‐Qian; Chen, Yu‐Hong; Wang, Jing‐Zhi; Xu, Zheng‐Li; et al.
Summary: Haploidentical allogeneic haematopoietic stem cell transplantation (haplo‐HSCT) is a significant alternative treatment for severe aplastic anaemia (SAA). To improve this process by modifying the risk stratification system, we conducted a retrospective study using our database. 432 SAA patients who received haplo‐HSCT between 2006 and 2020 were enrolled. These patients were divided into a training ( n  = 288) and a validation ( n  = 144) subset randomly. In the training cohort, longer time from diagnosis to transplantation, poorer Eastern Cooperative Oncology Group (ECOG) status and higher haematopoietic cell transplantation‐specific comorbidity index (HCT‐CI) score were independent risk factors for worse treatment‐related mortality (TRM) in the final multivariable model. The haplo‐HSCT scoring system was developed by these three parameters. Three‐year TRM after haplo‐HSCT were 6% [95% confidence interval (CI), 1–21%], 21% (95% CI, 7–40%), and 47% (95% CI, 20–70%) for the low‐, intermediate‐, and high‐risk group, respectively ( P  < 0·0001). In the validation cohort, the haplo‐HSCT scoring system also separated patients into three risk groups with increasing risk of TRM: intermediate‐risk [hazard ratio (HR) 2·45, 95% CI, 0·92–6·53] and high‐risk (HR 11·74, 95% CI, 3·07–44·89) compared with the low‐risk group ( P  = 0·001). In conclusion, the haplo‐HSCT scoring system could effectively predict TRM after transplantation.